Folate Anchored Nanostructured Lipid Carrier for Lung A549 Adenocarcinoma Cell Targeting - Rajoriya, Vaibhav; Gupta, Ravikant (Journal of Neonatal Surgery, 2025)
Background: Nanomedicine faces significant challenges in targeted drug delivery using nanocarriers. The background of this approach lies in addressing the challenges of conventional chemotherapy, such as systemic toxicity, poor bioavailability, and drug resistance. Nanostructured lipid carriers (NLCs) are advantageous due to their biocompatibility, ability to encapsulate both hydrophilic and lipophilic drugs, and controlled drug release properties. Folate conjugation further enhances the specificity of these carriers, making them a promising tool for lung cancer treatment. Objective: A newly developed folate-anchored nanostructured lipid carrier (F-NLCs) with pegylated polymer shows potential in enhancing targeting efficiency toward cancer cells and minimizing drug-related side effects. Method: This study evaluates the impact of F-NLCs on A549 lung adenocarcinoma cells using the SRB assay method. Paclitaxel, a widely-used anticancer agent, was incorporated into F-NLCs via the ethanol injection technique. Result: The formulations were characterized for particle size and zeta potential, and their cancer targeting potential was assessed on A549 cells. F-NLCs displayed a particle size of 231.11±2.3 nm and a zeta potential of 10.2±0.3 mV. These carriers exhibited the highest cell growth inhibition rates compared to P-NLCs formulations, with a dose-dependent inhibition observed in A549 cells. Increased drug concentration in cancer cells was noted, likely due to receptor-specific targeting facilitated by folate conjugation. Conclusion: F-NLCs represent a stable, secure, and potentially effective drug delivery system for lung cancer targeting, showcasing enhanced uptake and inhibition of cancer cells.